Uma contribuição à reformulação da norma regulamentadora 13 (NR-13) na perspectiva da adoção de sistema de gestão de segurança e saúde ocupacional - Sousa, Edilson Rocha de (2008)
This Master s Thesis deals with an analysis of the Regulatory Standards NR-9 e NR-13 on the perspective of occupational health and safety management systems (OHSMS) such as ILO deployed ILO/OSH-2001. Since the revamped OHSAS 18001:2007 complies with the ILO/OSH-2001 model it is used as benchmark to compare against the NR-9 and NR-13. The analysis suggests that the NR-9 has some important features present on the OHSAS 18001:2007 but lacks important others. The NR-13 turns out to be far from a modern model of OHSMS such as OHSAS 18001:2007 and a deep reformulation should be done in order to achieve the Brazil commitment with ILO to adopt OHSMS. Also, a small survey with companies with ISO 9000 certificates suggests that a NR-13 revised toward OHSMS would be welcome, but also that some more advanced issues present in ILO/OSH-2001 should be imposed by law in order to be achieved